[PP.37.08] HEALTHY LIFESTYLE IS ASSOCIATED WITH LOWER RISK OF EARLY VASCULAR AGEING: THE OPTIMO STUDY IN LATIN AMERICA. (September 2016) - Nilsson, P.M.; Scuteri, A.; Botto, F.; Obregon, S.; Forcada, P.; Koretzky, M.; Di Leva, A.; Huguet, E.; Haehnel, M.; Waisman, G.; Kotliar, C.
Abstract : Objective: Early Vascular Ageing (EVA), dominated by increased arterial stiffness, is a cardiovascular risk marker. Our aim was to elucidate on lifestyle factors associated with EVA in diverse populations across Latin America. Design and method: A total of 1044 city inhabitants (51.3% men, mean age 50.3 ± 15.3 years) underwent a health screening examination in 12 countries in Latin America (Argentina, Brazil, Chile, Colombia, Costa Rica, Guatemala, Honduras, México, Nicaragua, Panamá, República Dominicana, Salvador). This included anthropometrics, a questionnaire on lifestyle (WHO STEPS survey), medical history, and measurement of pulse wave velocity (PWV) for arterial stiffness (Mobil-O-Graph device). PWV values were transformed into age-specific z-scores to identify subjects with greater than age-peers PWV values, here defined as EVA. Age groups were defined based upon age quartiles of the study population (Q1: <42, Q2: 42–51, Q3: 52–60, and Q4: 61+ years). Within each age quartile, a z-score was defined as (individual PWV – age-quartile mean PWV)/ age-quartile SD of PWV). Results: PWV ranged from 4.1 to 15.0 m/s and correlated with age (r = 0.81, p < 0.0001), as expected. PWV average values (mean, SD) were for age quartiles: Q1: 6.0 ± 1.6; Q2: 6.7 ± 0.7; Q3: 7.9 ± 0.7; and Q4: 9.8 ± 1.5 m/s. A consumption of fruit greater than 7 servings/week (beta-coefficient -0.118 ± 0.061, p < 0.05) and physical activity (day per week) (beta-coefficient -0.032 ± 0.013, p < 0.01) were independent and significant determinants of the PWV z-score treated as a continuous variable, after controlling for age, sex and risk factors. When the likelihood of having a PWV z-score above the median (indicating EVA) was modelled, fruit consumption lost significance (odds ratio (OR) 0.99, 95% CI: 0.65–1.50). However, physical activity (OR 0.91, 95% CI: 0.83–0.99, p < 0.05) and a daily intake of seeds (OR 0.63, 95% CI: 0.41–0.96, p < 0.01) were still associated with reduced risk of EVA. This corresponded to the equivalent of having a 4 to10 year younger arterial system in subjects reporting healthy lifestyle. Conclusions: A healthy lifestyle was associated with lower risk of age- and risk factor adjusted PWV (arterial stiffness) as the core component of EVA in a diverse population from across Latin America.